Print advertising of cosmetics in Spain and its visual characteristics - Cerdá-Vilaplana, Marina; Ortiz-Diazguerra, María Jesús; Vilaplana-Aparicio, María José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This study uses the content analysis to understand the visual aspects of print advertising in the category "Facial beauty treatments" of the main brands in Spain. The data indicate that the most used structure is the image of a woman who personifies the ideal of beauty on the left, while on the right is located the explanatory text together with the product, usually represented in an expressive way. In addition, each brand is characterized by a specific combination of visual strategies. The results have implications both for the advertising sector and for visual culture studies.